Towards Reliable Methodology: Microbiome Analysis of Fresh Frozen vs. Formalin-Fixed Paraffin-Embedded Bladder Tissue Samples: A Feasibility Study - Dominik Enderlin; Uwe Bieri; Jana Gadient; Yasser Morsy; Michael Scharl; Jan Hendrik Rüschoff; Lukas John Hefermehl; Anna Nikitin; Janine Langenauer; Daniel Stephan Engeler; Beat Förster; Fabian Obrecht; et al. (Microorganisms)
Studies have shown that the human microbiome influences the response to systemic immunotherapy. However, only scarce data exist on the impact of the urinary microbiome on the response rates of bladder cancer (BC) to local Bacillus Calmette-Guérin instillation therapy. We launched the prospective SILENT-EMPIRE study in 2022 to address this question. We report the results of the pilot study of SILENT-EMPIRE, which aimed to compare the microbiome between fresh frozen (FF) and formalin-fixed paraffin-embedded (FFPE) samples in the cancerous tissue and adjacent healthy tissue of BC patients. Our results show that alpha diversity is increased in FF samples compared to FFPE (coverage index p = 0.041, core abundance index p = 0.008). No significant differences concerning alpha diversity could be detected between cancerous and non-cancerous tissue in the same BC patients. This study demonstrates that microbiome analysis from both FF and FFPE samples is feasible. Implementing this finding could aid in the translation of research findings into clinical practice.